Law Enforcement Against Perpetrators of the Criminal Offense of Religious Blasphemy Committed through Social Media (A Study at the North Sumatra Regional Police) - Meta Junita Nababan; Rizkan Zulyadi; Serimin Pinem (Journal of Public Representative and Society Provision, 2026)
This research is entitled Law Enforcement Against Religious Criminal Acts of Blasphemy Committed Through Social Media (North Sumatra Regional Police Study). The formulation of the problem is (1) What are the legal rules for criminal acts of blasphemy based on statutory regulations? (2) How is the law enforcement process carried out by the North Sumatra Regional Police against perpetrators of criminal acts of blasphemy through social media? (3) What are the obstacles faced by the North Sumatra Regional Police in enforcing the law against perpetrators of criminal acts of blasphemy through social media? The research method used is normative juridical legal research, with a descriptive analytical research type. To approach the problem, a normative juridical approach is used. The data used are primary and secondary data. The results of the study show that (1) The legal rules for criminal acts of blasphemy are regulated in Article 29 of the 1945 Constitution, Presidential Decree of the Republic of Indonesia No. 1/PNPS of 1965 concerning the Prevention of Abuse of Blasphemy, Article 156a of the Criminal Code, and Law No. 11 of 2008 concerning Electronic Information and Transactions. (2) The law enforcement process carried out by the North Sumatra Regional Police against perpetrators of the crime of blasphemy through social media is when the North Sumatra Regional Police receive a report regarding blasphemy from the community who has been harmed, the North Sumatra Regional Police will conduct an investigation by collecting initial evidence to determine whether or not there are criminal elements. If the elements are met, it will proceed to the investigation stage. (3) The obstacles faced by the North Sumatra Regional Police in enforcing the law against perpetrators of the crime of blasphemy are the existence of articles that are open to multiple interpretations, namely Article 156 of the Criminal Code and the ITE Law, which are often considered to have broad formulations, giving rise to differences in interpretation - what is considered "blasphemy" in one case, can be considered "criticism" or "opinion" in another case.